Implementasi Pembelajaran Berbasis Proyek Untuk Mengembangkan Karakter Tanggung Jawab Di Kelas Inklusif - Bella Astridarani; Muhammad Fauzan Muttaqin (CV. SINAR HOWUHOWU, 2026)
This study aims to describe the implementation of Project-Based Learning in developing students’ responsibility character in an inclusive classroom. This research is grounded in the importance of fostering responsibility as a key 21st-century competence, particularly in learning environments that accommodate diverse student abilities, needs, and characteristics. A qualitative descriptive approach was employed in this study. The participants consisted of teachers and students in an inclusive classroom. Data were collected through observation, interviews, and documentation. The findings reveal that the implementation of Project-Based Learning enhances students’ sense of responsibility, as reflected in their active involvement in planning, implementing, and completing project tasks, as well as in their ability to collaborate and fulfill their assigned roles. Furthermore, students with special needs demonstrated improvements in independence and commitment to their learning tasks. Project-Based Learning provides equal opportunities for all students to participate according to their abilities, thereby fostering an inclusive learning environment that supports character development. Therefore, Project-Based Learning is an effective instructional strategy for developing students’ responsibility character in inclusive classrooms.